RELIGIUSITAS DALAM SYAIR AYYA MAN YADDAIL FAHM KARYA AL-HARIRI: RELIGIOSITY IN THE POEM AYYA MAN YADDA’IL FAHM BY AL-HARIRI - Harlan Darmawan; Fadlil Yani Ainusyamsi; Ade Ahmad Suprianto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research is motivated by the pervasive dominance of contemporary materialistic culture which creates the phenomenon of simulacra, where transcendental values are often obscured by shallow imagery that has lost its referential reference to the divine. In response to this spiritual crisis, this study aims to uncover the systematic construction of religiosity in the classic poem Ayya Man Yadda’il Fahm by Al-Hariri through the triadic semiotic approach of Charles Sanders Peirce. The research method employed is a descriptive qualitative approach utilizing the interactive model analysis procedure of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing/verification. The results show that the sign mechanism in the poem is massively dominated by Index signs which have physical causality relationships, particularly within the indicators of Piety (Takwa) and Repentance (Tobat). Al-Hariri strategically utilizes biological "bluffing" through irrefutable existential facts, such as the appearance of gray hair as a sign of aging and the absolute certainty of death, to force the reader into an immediate confrontation with eschatological reality. The research conclusion confirms that the dominance of these indexical signs functions as an effective social critique instrument to dismantle the simulacra of modern culture through a profound spiritual shock effect. This approach provides a more precise and scientific analytical depth than previous stylistic or linguistic studies because it is capable of dissecting how the triadic sign structure—Representament, Object, and Interpretant—transforms mortal biological objects into a semiotic means to understand the eternal Essence of Allah. Therefore, this study offers a new perspective in understanding classical Arabic literature as a relevant medium for contemporary character education and spiritual awakening.